2024
DOI: 10.1111/nph.19861
|View full text |Cite
|
Sign up to set email alerts
|

Multiple deletions of candidate effector genes lead to the breakdown of partial grapevine resistance to downy mildew

Manon Paineau,
Andrea Minio,
Pere Mestre
et al.

Abstract: Summary Grapevine downy mildew, caused by the oomycete Plasmopara viticola (P. viticola, Berk. & M. A. Curtis; Berl. & De Toni), is a global threat to Eurasian wine grapes Vitis vinifera. Although resistant grapevine varieties are becoming more accessible, P. viticola populations are rapidly evolving to overcome these resistances. We aimed to uncover avirulence genes related to Rpv3.1‐mediated grapevine resistance. We sequenced the genomes and characterized the development of 136 P. viticola strains on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 84 publications
0
1
0
Order By: Relevance
“…LOH can provide an additional way of adaptation during the growing season, through the fixation of beneficial alleles faster than annual sexual reproduction. For example, important traits such as fungicide tolerance and virulence are determined by co-dominant or recessive alleles (Lamour et al, 2012;Matson et al, 2022;Paineau et al, 2024). It has been shown that LOH can lead to a gain of virulence in Pe.…”
Section: Adaptation By Loss Of Heterozygositymentioning
confidence: 99%
“…LOH can provide an additional way of adaptation during the growing season, through the fixation of beneficial alleles faster than annual sexual reproduction. For example, important traits such as fungicide tolerance and virulence are determined by co-dominant or recessive alleles (Lamour et al, 2012;Matson et al, 2022;Paineau et al, 2024). It has been shown that LOH can lead to a gain of virulence in Pe.…”
Section: Adaptation By Loss Of Heterozygositymentioning
confidence: 99%